Cardiac myocyte miR-29 promotes pathological remodeling of the heart by activating Wnt signaling. Issue 1 (December 2017) - Sassi, Yassine; Avramopoulos, Petros; Ramanujam, Deepak; Grüter, Laurenz; Werfel, Stanislas; Giosele, Simon; Brunner, Andreas-David; Esfandyari, Dena; Papadopoulou, Aikaterini; Strooper, Bart; Hübner, Norbert; Kumarswamy, Regalla; et al.
Abstract Chronic cardiac stress induces pathologic hypertrophy and fibrosis of the myocardium. The microRNA-29 (miR-29) family has been found to prevent excess collagen expression in various organs, particularly through its function in fibroblasts. Here, we show that miR-29 promotes pathologic hypertrophy of cardiac myocytes and overall cardiac dysfunction. In a mouse model of cardiac pressure overload, global genetic deletion of miR-29 or antimiR-29 infusion prevents cardiac hypertrophy and fibrosis and improves cardiac function. Targeted deletion of miR-29 in cardiac myocytes in vivo also prevents cardiac hypertrophy and fibrosis, indicating that the function of miR-29 in cardiac myocytes dominates over that in non-myocyte cell types. Mechanistically, we found cardiac myocyte miR-29 to de-repress Wnt signaling by directly targeting four pathway factors. Our data suggests that, cell- or tissue-specific antimiR-29 delivery may have therapeutic value for pathological cardiac remodeling and fibrosis. MicroRNA-29 is known to reduce collagen production in fibroblasts thereby inhibiting fibrosis in various organs. Here, Sassi et al. show that miR-29 can also enhance fibrotic signalling and pathological hypertrophy of the heart through its action in cardiomyocytes.